Rancangan Sistem Stock Opname Berbasis Web pada PT. Exo Drinks Indonesia (Es Teler Sultan Bandung Outlet Ciledug) - Rizky Adi Kurniawan; Farizi Ilham; Ahmad Noval Septiansyah; Renno Alfaridzi (CV. Shofanah Media Berkah, 2026)
The rapid development of information technology has encouraged companies to improve the effectiveness and efficiency of data management, including inventory management. PT Exo Drinks Indonesia, particularly at the Es Teler Sultan Bandung Ciledug outlet, still conducts stock opname activities using a semi manual process by recording inventory data on personal devices before entering it into the Point of Sales (POS) system. This process may lead to recording errors, data duplication, reporting delays, and discrepancies between system records and actual physical stock. The purpose of this internship project is to design a web based stock opname system that can improve the effectiveness, efficiency, and accuracy of inventory management processes. The methods applied in this study include observation, interviews, documentation, system requirements analysis, system design, implementation, and testing using the Waterfall development approach. The proposed system provides features for inventory data management, stock-in and stock-out transactions, physical stock recording, automatic stock discrepancy calculations, and real-time reporting. The results indicate that the designed system can support an integrated stock opname process, minimize recording errors, accelerate data processing, and improve inventory information accuracy. The implementation of this system is expected to assist the company in monitoring inventory more effectively and supporting faster and more accurate decision-making processes.